Hubungan Manusia dan Lingkungan Kerja Fisik Sebagai Prediktor dalam Meningkatkan Kinerja Karyawan: Sebuah Investigasi Empiris - Muzakki, Muzakki (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2021)
This study aims to explore the relationship between human relations and physical work environment on employee performance. The method used is quantitative with an emphasis on hypothesis testing. The sample used in this study was 65 employees using the purposive random sampling method. The data analysis technique used was Structural Equation Modeling Partial Least Square (SEM-PLS). The findings of this study reveal that human relations and physical work environment both partially and simultaneously have a significant effect on employee performance. The results of this study also prove that the human relation variable has a dominant effect on improving employee performance. In addition, this study provides insights to organizations in designing appropriate systems to improve employee performance..